Nanomicelle formulation modifies the pharmacokinetic profiles and cardiac toxicity of daunorubicin. (2014) - Zhang, Hongyong; Li, Yuanpei; Lin, Tzu-yin; Xiao, Kai; Haddad, Ashraf S; Henderson, Paul T; Jonas, Brian A; Chen, Mingyi; Xiao, Wenwu; Liu, Ruiwu; Lam, Kit S; Pan, Chong-xian
Background: Treatment with daunorubicin (DNR) in acute myeloid leukemia is moderately effective and associated with significant side effects, including cardiac toxicity. We recently developed a nanomicellar formulation of DNR that specifically targets acute myeloid leukemia stem cells.Materials & methods: Pharmacokinetics analysis of free DNR, DNR in nanomicellar formulations was performed in Balb/c mice and Sprague–Dawley rats. Histochemical staining, caspase 3/7, troponin and creatine kinase MB isoenzyme were used to assess toxicity.Results: Compared with free DNR, the nanomicellar formulations of DNR had less cardiotoxicity as evidenced by milder histopathological changes, lower caspase 3/7 activity in heart tissue (p = 0.002), lower plasma creatine kinase MB isoenzyme (p = 0.002) and troponin concentrations (p = 0.001) postinjection. The area under curve concentration of DNR in micelles increased by 31.9-fold in mice (p < 0.0001) and 22.0-fold higher in rats (p < 0.001).Conclusion: Leukemia stem cell-targeting micelles dramatically change the pharmacokinetics and reduce the cardiac toxicity of DNR, which may enable improved DNR-based treatment of acute myeloid leukemia. Original submitted 24 January 2014; Revised submitted 28 February 2014